Manajemen Perubahan dan Implementasi dalam Proyek Sistem Informasi - Deby Nofriansyah; Nuri Islami (Universitas Muhammadiyah Enrekang, 2022)
The introduction or replacement of an information system and organizational behavioral impact is very complicated. Changes in how information is defined, accessed, and used to manage organizational resources often result in power sharing and a new strength. This condition is usually caused by mistakes in managing the transition phase. A process of change and implementation have a psychological impact on those affected by change (internal), where if the changes actually happen, will cause the impact of situational for others associated with the organization. Control project risk factors to some extent by the approach just in case. This research uses the concept of integrated project management with a total solution approach, namely awareness, alignment, action, adoption, assurance. This total solution approach through four important stages, namely the determination of the diagnostic phase, redesigning the organization, organizational transformation and continuous improvement with diagrams aids Delta Matrix. Overall information system design and implementation process should be managed as a planned organizational change. Social and technical design aims to obtain an optimal combination of design solutions to social and technical. Key to the success of change management and implementation also relies heavily on the company's commitment, communication skills, focus on implementing change and not be bothered with other things, and utilize human resources to be able to implement the change process and implementation.